Knowledge and awareness of parasitic worms among biology student-mothers in Zaria, Nigeria - Nuru, Ramatu Asabe; Lawal, Saadatu Bagiwa; Adamu, Tairu Arome (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study titled Biology Student-Mothers Knowledge and Awareness of Parasitic Worms Affecting Children in Zaria, Nigeria was a survey work carried out at the Federal College of Education, Zaria. Three research objectives and three research questions guided the study. The sample for the study comprised two hundred and thirty-six biology student-mothers drawn from a population of two thousand and thirty-four using a purposive sampling technique. The data collection instrument utilized in this study was a questionnaire titled the Student-Mothers Awareness of Parasitic Worms Questionnaire (SMAPWQ). The questionnaire underwent validation by two experienced science education experts. Split-half method was used to determine the reliability resulting in a Cronbach alpha value of 0.71. The instrument was distributed to student mothers over two weeks. The data gathered was analysed using mean and standard deviation. The results revealed that there is a high awareness level among student-mothers on parasitic worms in Zaria (M=3.02, SD = 1.0), roundworm, hookworm and tapeworm were the major types of worms that affect children of biology student-mothers in Zaria, and there is high knowledge level on eradication and control of parasitic worms among Biology student-mothers in Zaria (M=3.71, SD = 0.86). This research recommends that the management of FCE, Zaria and the Department of Biology should provide targeted educational interventions and public health awareness campaigns on managing parasitic infections for all members of the College community, among others.